PENERAPAN PENDEKATAN KONTEKSUAL MENGGUNAKAN MODEL KOOPERATIF TIPE THINK PAIR SHARE TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP DI KOTA CIMAHI - Senjayawati, Eka (IKIP Siliwangi, 2020)
This study aims to determine whether the mathematical problem solving ability of junior high school students who use a contextual approach with the cooperative model of think pair share type is better than the scientific approach. The subject of the study was the eighth grade junior high school students in Cimahi, while the sample was class VIII B as an experimental class that got learning using a contextual approach with a cooperative model of think pair share type and class VIII C became a control class that got learning using a scientific approach. The instrument in the study was a matter of mathematical problem solving ability consisting of five item description items. Based on the results of all stages of the study, it can be concluded that the mathematical problem solving ability of students whose learning uses a contextual approach through a cooperative model of think pair share type is better than that of learning using a scientific approach.Â